La calidad de los servicios de la biblioteca del área de la salud humana de la Universidad Nacional de Loja y su incidencia en la satisfacción de las necesidades de información de los usuarios de la biblioteca durante el período julio a diciembre del 2012 - Maza, Margoth Elizabeth (2013)
The present investigation called: THE QUALITY OF THE LIBRARY IN THE AREA OF HEALTH SERVICES HUMAN NATIONAL UNIVERSITY OF LOJA AND ITS IMPACT ON THE SATISFACTION OF THE INFORMATION NEEDS OF THE USERS OF THE LIBRARY DURING THE PERIOD JULY TO DECEMBER 2012. This research work has as main objective to determine the incidence between the quality of library services Area of Human Health and the information needs of users. It raised a general objective to determine the degree of satisfaction of users of the area of Human Health at the National University of Loja in reciprocity to the quality of services received and propose guidelines to improve library services. In the methodology used the following research methods were scientific, analytic-synthetic, inductive, deductive, and Statistical. The techniques used were: the interview to staff working in the library and a survey of students of different races. With a sample of 387 which corresponds to 20% of students of different races in the area enrolled in 2012. It is concluded that 78% of students surveyed indicated that the quality of services offered by the library does not meet your information needs, considering user satisfaction depends on the quality of service provided. In the interview with the staff working in the library was observed that 100% are in agreement that if you provide quality services. Analyzing survey and interview there is a discrepancy between what he says library staff regarding the views of users, in terms of updating the bibliographic material and technological resources.